Identifikasi Kesesuaian Nilai Ganti Rugi Pengadaan Tanah Untuk Kepentingan Umum (Studi Kasus : Normalisasi Sungai Cilember Kecamatan Margaasih, Kabupaten Bandung): Identifikasi Kesesuaian Nilai Ganti Rugi Pengadaan Tanah Untuk Kepentingan Umum (Studi Kasus : Normalisasi Sungai Cilember Kecamatan Margaasih, Kabupaten Bandung) - Towus Firdaus (Bandung Conference Series: Urban & Regional Planning, 2023)
Abstract.Procurement of Cilember River Land is one of the indicators of the river normalization program in accordance with governor regulation No. 37 of 2021 concerning action plans to control pollution and damage to the Citarum River Basin. In land acquisition activities, the value of compensation is one of the most important aspects as well as a concern for affected residents about the compensation value they will receive later. Therefore, it is necessary to match the value of compensation based on the regulations governing the wishes of the affected residents. In the land acquisition mechanism in the ATR/BPN Ministerial Regulation No. 19 of 2021 concerning procedures for implementing land acquisition that everything that is above and below the ground needs to be calculated for its replacement value including buildings, land and growing plants. The approach taken in calculating the value of compensation refers to the Land Value Zone (ZNT), the market price of buildings in the affected area, the Cilember River land acquisition planning document (UPTD PSDA WS Citarum), SPI 306 Indonesian Appraisal Professional Society and the MOU or Letter of Agreement between Bandung Regency Government and West Java Provincial Government. From the results of the analysis of the value of compensation, the West Java provincial government must provide a budget of at least Rp. 62.716.894.801 and the maximum value is Rp. 74.913.958.683 as a fair replacement value to replace physical and non-physical losses from residents affected by land acquisition for the normalization of the Cilember River in an effort to minimize flood disasters. Abstrak. Pengadaan Tanah Sungai Cilember merupakan salah satu indikator program normalisasi sungai sesuai dengan peratura gubernur No 37. Tahun 2021 tentang rencana aksi pengendalian pencemaran dan kerusakan Daerah Aliran Sungai Citarum. Dalam kegiatan pengadaan tanah nilai ganti rugi menjadi salah satu aspek yang paling penting sekaligus menjadi kekhawatiran warga terdampak terhadap nilai penggantian yang nantinya mereka terima. Maka dari itu perlu adanya kesesuaian nilai ganti rugi berdasarkan peraturan yang mengatur dengan keinginan warga terdampak. Dalam mekanisme pengadaan tanah pada peraturan Menteri ATR/BPN No. 19 Tahun 2021 tentang tata cara pelaksanaan pengadaan tanah bahwa segala sesuatu yang berada diatas dan dibawah tanah perlu dihitung nilai penggantiannya meliputi bangunan, tanah dan tanam tumbuh. Adapun pendekatan yang dilakukan dalam menghitung nilai ganti rugi tersebut mengacu pada Zona Nilai Tanah (ZNT), Harga pasar banguanan wilayah terdampak, dokumen perencanaan pengadaan tanah Sungai Cilember (UPTD PSDA WS Citarum) , SPI 306 Masyarakat Profesi Penilai Indonesia dan MOU atau Surat Kesepakatan antara Pemerintah Kabupaten Bandung dan Pemerintah Provinsi Jawa Barat. Dari hasil analisis nilai ganti rugi pemerintah Provinsi Jawa Barat harus menyediakan anggaran sebesar minimal Rp. 62.716.894.801 dan nilai maksimum yaitu Rp. 74.913.958.683 sebagai nilai penggantian wajar untuk mengganti kerugian fisik dan non fisik dari warga terdampak pengadaan tanah untuk normalisasi ungai Cilember dalam upaya meminimalisir bencana banjir.